Aesthetic judgment and the moral image of the world: Studies in Kant - Henrich, Dieter (Stanford Stanford series in Philosophy, 1992)
This is a collection of four essays on aesthetic, ethical, and political issues by Dieter Henrich, the preeminent Kant scholar in Germany today. Although his interests have ranged widely, he is perhaps best known for rekindling interest in the great classical German tradition from Kant to Hegel. The first essay summarizes Henrich's researches into the development of Kant's moral philosophy. It shows that the architecture of the third Critique depends upon a change in Kant's notion of a philosophical system, which in turn emerged from an important change in the foundation of Kant's moral philosophy. This change is shown to occur in the course of his work and reflections on the "Groundwork of the Metaphysics of Morals." Of special interest in this essay is Henrich's intriguing and wholly new account of the relation between Kant and Rousseau. In the second essay, Henrich analyzes the interrelations between Kant's aesthetics and his cognitive theories, concluding that though Kant has opened up an important and fruitful avenue of questioning, the problems he addresses are not yet resolved. Henrich is convinced that "even after two hundred years it remains promising to pursue such a ?Kantian? program." The third essay argues that the justification of the claim that human rights are universally valid requires reference to a moral image of the world. To employ Kant's notion of a moral image of the world without ignoring the insights and experiences of this century requires, to be sure, drastic changes in the content of such an image, but Henrich explains, at least in part, what its content might be for our time. In an ambitious concluding essay, Henrich compares the development of the political process of the French Revolution and the course of classical German philosophy, raises the general question of the relation between political processes and theorizing, and argues that both the project of political liberty set in motion by the French Revolution and the projects of classical German philosophy remain incomplete.